Coastlines of the Eastern Arctic - Sempels, Jean-Marie (ARCTIC, 1982)
A computer approach was developed and used to analyse the characteristics of coastlines present in the eastern Arctic. Results of this analysis indicate that: 1) almost 75% of all coastlines include a beach; 2) backshores are mostly steep and made up of bedrock; 3) beaches are made up mostly of coarse sediments; 4) the most abundant types of coastal zones consist of steep rocky backshores without beach, and steep rocky backshores with colluvium and continuous boulder beaches; 5) the average slope of backshores and the size of the dominant beach sediment decrease towards the north; 6) fetch has little influence on coastal characteristics; and 7) coastal characteristics are determined primarily by the physiography of the adjacent land and by the nature of backshores.Key words: eastern Arctic, coastlines, geomorphology Mots clés: l'Arctique de l'est, côtes, géomorphologie